واقع و أثر الإبتكار التسويقي على الميزة التنافسية في المؤسسات الخدماتية: دراسة حالة - مؤسسة اتصالات الجزائر خلال الفترة 2022-2023 - ميدون سيساني (جامعة الوادي University Of Eloued, 2024)
The new world is witnessing a complex environment for business, where creativity and marketing innovation have taken a great place and are considered as distinctive field in economic company, which aims to develop its competitive advantages. And this research paper sheds light on the study of the impact of marketing innovation on granting elements of superiority and promotion and marketing position to Algeria Telecom Corporation through the results showing us that there is a statistically significant relationship between marketing innovation and achieving competitive advantage at the significance level 0.05 ≤ α. Where the result of the correlation coefficient between them was estimated at 0.809, which has a significant statistical significance since the Sig value is the probability of the relationship between the two variables. On the other hand, the value of Fisher F achieved significant significance Sig = 0.000, which indicates the overall validity of the model.
The reality and impact of marketing innovation on the competitive advantage in service organizations: Case study - Algeria Telecom Corporation during the period 2022-2023
Keywords: بيئة الأعمال; الابتكار التسويقي; التنافسية; Business environment; Marketing innovation; Competitiveness